Stephen Hawking's A brief history of time : a reader's companion - Hawking, Stephen (New York : Bantam Books, 1995)
Contains personal interviews of nine people who know Professor Hawking describing him, his life, and work, finally Professor Hawking talks about himself
Keywords: Cosmologie; Scientists; Biography Universe